Presuposisi Potensial Mengandung Gaya Bahasa sebagai Kontrol Rasionalisasi Tuturan pada Podcast Denny Sumargo - Yuanita Widiastuti; Moh. Badrih; Hasan Busri (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2023)
Denny Sumargo's podcast has become one of the most popular channels for various people. One of the interesting topics that can be studied is the potential presuppositions that appear in speech. Denny Sumargo discoursed with his interlocutor through the use of certain figurative speech. The aim of this study is to analyze the figurative speech control rationale of potential presuppositional found on Denny Sumargo’s YouTube podcast channel with Laura Anna. The research method used in this study was content analysis with a qualitative approach. The data was taken from discourse activities on the video podcast of Denny Sumargo with Laura Anna which aired on Youtube. The data in this study was a discourse that contained potential presuppositions. Data collection techniques in the study were carried out with documentation techniques, listening techniques, and note-taking techniques. Based on the data analysis, it was found that all types of potential presuppositions were in the style of repetition, ellipsis, symbolism, hyperbole, euphemism, and metaphor. Those potential presuppositions of figurative speech aim to soften the language so that the interlocutor does not feel offended, to confirm the intention, to trigger interpretation, and to enhance the impression. Those a forms of rationalization of speech to control the social attributes of Laura Anna as a guest star who is paralyzed due to an accident.